THE RELATIONSHIPS BETWEEN SUPPLIER PARTNERSHIP, ENVIRONMENTAL VARIABLES ANDFIRM PERFORMANCE IN RETAIL INDUSTRY - Soehadi, Agus W. (Gadjah Mada International Journal of Business, 2003)
Partnership with suppliers is becoming a critical activity in retail industry to strengthen their competitive position. However, evidence suggested that partnership efforts do not reach their potential due to the effect of external factors. This article presents a comprehensive model that depicts the links among the supplier partnership, environmental variables and firm performance. Data for testing the model were collected by sending a questionnaire to a sample of retail industry in Indonesia. Hypothesized links depicted in the research model were tested using structural equation modeling. The findings show that supplier partnership affects positively firm performance in general term as well as across components of performance measurement. The empirical results suggest that the effect of environmental variables on supplier partnership is: market turbulence has a positive effect, competitive intensity and demand volatility have a negative effect.